Village Barn in Coastal Area of Java, From “Lumbung Desa” to Village Unit Cooperative in Demak-Grobogan - Endah Sri Hartatik; Wasino Wasino; Tri Handayani; Sri Sudarsih (Paramita: Historical Studies Journal, 2023)
This study aims to analyze the history of institutional changes in food security in the form of savings institutions at the micro-level of rural Indonesia. This research uses the history method using primary sources from documents and oral interviews. The traditional food security institutions in the form of Village Barns could run well because of the support and independence of rural communities. It happened during the colonial period until the beginning of Indonesian independence. After the emergence of modern logistics institutions in the form of the Logistics Affairs Agency (Bulog) and KUD, which were the result of the policies of the New Order government, rural communities became independent. They depended on the government for fertilizers, medicines, seeds, and others. With the presence of these modern logistics institutions, community-based resilience institutions are increasingly marginalized. Its findings indicate a difference in effectiveness between traditional food security institutions and current resilience institutions in ensuring the availability of rice in rural areas. The government needs to re-strengthen community participation-based savings institutions through village granaries.Penelitian ini bertujuan untuk menganalisis sejarah perubahan kelembagaan ketahanan pangan berupa lembaga tabungan pada tingkat mikro di pedesaan Indonesia. Penelitian ini menggunakan metode sejarah dengan menggunakan sumber primer berupa dokumen dan wawancara lisan. Kelembagaan ketahanan pangan tradisional berupa Lumbung Desa dapat berjalan dengan baik karena adanya dukungan dan kemandirian masyarakat pedesaan. Hal itu terjadi pada masa penjajahan hingga awal kemerdekaan Indonesia. Setelah munculnya lembaga logistik modern berupa Badan Urusan Logistik (Bulog) dan KUD yang merupakan hasil kebijakan pemerintah Orde Baru, masyarakat pedesaan menjadi mandiri. Mereka bergantung pada pemerintah untuk pupuk, obat-obatan, benih, dan lain-lain. Dengan hadirnya lembaga logistik modern tersebut, lembaga ketahanan berbasis masyarakat semakin terpinggirkan. Temuan-temuan penelitian ini menunjukkan adanya perbedaan efektivitas antara lembaga ketahanan pangan tradisional dan lembaga ketahanan pangan saat ini dalam menjamin ketersediaan beras di daerah pedesaan. Pemerintah perlu kembali memperkuat lembaga tabungan berbasis partisipasi masyarakat melalui lumbung desa.